Bias in the estimation of mean reversion in continuous-time Levy processes - BAO, Yong (Institutional Knowledge at Singapore Management University, 2015)
This paper develops the approximate bias of the ordinary least squares estimator of the mean reversion parameter in continuous-time Levy processes. Several cases are considered, depending on whether the long-run mean is known or unknown and whether the initial condition is fixed or random. The approximate bias is used to construct a bias corrected estimator. The performance of the approximate bias and the bias corrected estimator is examined using simulated data.